A new species of Asiophlugis (Orthoptera: Tettigoniidae: Phlugidini) from Misamis Oriental (Philippines, Mindanao) - Tan, Ming Kai; Salvador, Jewel Anne G.; Nuñeza, Olga Macas (Zootaxa, 2023)
A new species of Asiophlugis Gorochov, 1998 (Orthoptera, Tettigoniidae, Phlugidini) is described from southern Philippines, in Mindanao, Misamis Oriental, Gingoog City: Asiophlugis spatulata sp. nov. This new species is characterised by the long, slender and flattened male cercus, with a basal process spatulated at the apex, and with a tooth-like medial process produced along the inner margin; as well as the male tenth abdominal tergite with two long cylindrical latero-apical processes pointing dorsad and externally. This new species represents the second species of Asiophlugis to be recorded from the Philippines.